International monetary regimes and the German model - Fritz W. Scharpf (Max Planck Institute for the Study of Societies, 2018)
The end of the Bretton Woods regime and the fall of the Iron Curtain deepened the export orientation of the German model of the economy. Only after entry into the Monetary Union, however, did rising exports turn into a persistent export-import gap that became a problem for other eurozone economies. This Discussion Paper shows why the present asymmetric euro regime will not be able to enforce their structural transformation on the German model. Neither will German governments be able to respond to demands that would bring the performance of the German economy closer to eurozone averages. Instead, it is more likely that present initiatives for financial and fiscal risk sharing will transform the Monetary Union into a transfer union. – – Das Ende des Bretton-Woods-Regimes und der Fall des Eisernen Vorhangs vertieften die Export-Orientierung der deutschen Wirtschaft. Aber erst unter der Währungsunion führten deutsche Exporte zu einer dauerhaften Export-Import-Lücke und erzeugten damit ein Problem für die anderen Mitgliedsländer. Das asymmetrische Euro-Regime kann deren strukturelle Transformation nach deutschem Vorbild nicht erzwingen. Ebenso wenig könnte die deutsche Politik eine strukturelle Transformation des deutschen Modells erreichen. Wahrscheinlicher ist es, dass die gegenwärtigen Initiativen zur finanziellen und fiskalischen Risikoteilung die Währungsunion zur Transferunion verändern werden.
hdl:21.11116/0000-0000-779C-B
Keywords: 300; German model; export surpluses; currency regimes; Monetary Union; structural divergence; risk sharing; deutsches Modell; Exportüberschüsse; Währungsregime; Währungsunion; strukturelle Divergenz; Risikoteilung